2023
DOI: 10.3390/app13021097
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Three Types of Disinfectants on the Microbial Flora from the Surface of Impression Materials Used in Dentistry—In Vitro Study

Abstract: During impressions, bacteria, viruses, and fungi remain on the impression material, representing a significant risk for the medical team (dentists, dental assistants, and laboratory technicians). Impression disinfectants have been introduced into dentistry to reduce the risk of cross-infection. This study was performed by examining the surface disinfection of five commonly used impression materials in prosthodontics: alginate-Tropicalgin (Zhermack®), condensation silicone-Zetaplus (Zhermack®), Oranwash L (Zher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…On the surface of every impression that was cleaned with this spray, several bacterial colonies were found. [ 3 ] Wezgowiec et al . concluded that UVC radiation, gaseous ozone, and liquid chemicals are effective disinfectants for impression sterilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the surface of every impression that was cleaned with this spray, several bacterial colonies were found. [ 3 ] Wezgowiec et al . concluded that UVC radiation, gaseous ozone, and liquid chemicals are effective disinfectants for impression sterilization.…”
Section: Discussionmentioning
confidence: 99%
“…Disinfection of the impression materials can be performed with either; chemical agents such as sodium hypochlorite, glutaraldehyde, radiation, herbal, autoclave, or ozone method. [ 1 2 3 ] Impression can be sterilized either by immersion or spraying technique. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%